The Impact of Digital Learning on Private School from Perspective of Technology Acceptance Model - Hussein Azeez, Hayder; ., .; ., . (International Journal of Engineering and Technology, 2018)
Despite the difficulties, risk and failures, higher education institutions are continuously replacing/implementing digital Systems to meet the demands of sector competition and expectation forming the stakeholders. Many literatures claim that the digital implementation is risky and challenging. Especially when HEIs are novice, it becomes important to mitigate the risk involved in digital implementation for a successful implementation. This paper proposes a new risk based framework for digital implementation in higher education.